1997
DOI: 10.1254/jjp.75.21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sucralfate and Its Components on Acid- and Pepsin-Induced Damage to Rat Gastric Epithelial Cells.

Abstract: ABSTRACT-Wehave established models of cell damage induced by acid and pepsin using rat gastric epithelial cells (RGMI). In the present study, the effects of aluminum hydroxide [AI(OH)3] and potassium sucrose octasulfate (KSOS), which are components of sucralfate, and sucralfate on cell damage and peptic activity of pepsin were examined. Pretreatment of cells with sucralfate (0.1-3 mg/ml) or Al(OH)3 (0.1-1 mg/ml) for 2 hr prevented both acid (pH 4.0) and pepsin (pH 4.5) induced cell damage. However, KSOS (0.1-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…These diverging results are discussed further below. In contrast with our data, some authors have shown an increase of gastric mitochondrial function using the MTT assay, following concomitant incubation with sucralfate and indomethacin . These contradictory findings could be explained by differences between several parameters including the concentration of MTT, the duration of incubation, or the number of viable cells and their metabolic activity.…”
Section: Discussioncontrasting
confidence: 99%
“…These diverging results are discussed further below. In contrast with our data, some authors have shown an increase of gastric mitochondrial function using the MTT assay, following concomitant incubation with sucralfate and indomethacin . These contradictory findings could be explained by differences between several parameters including the concentration of MTT, the duration of incubation, or the number of viable cells and their metabolic activity.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to its ability to induce PG synthesis, 18,19) this drug was shown to adhere to gastric mucosa directly and form a physical barrier against gastric irritants, 20,21) which distinguish it from the actions of other gastroprotective drugs. In addition to various mechanisms for its cytoprotective effects, such as detoxification and stimulation of mucus secretion and synthesis, [22][23][24] sucralfate was shown to protect gastric mucosal cells from gastric irritants (NSAIDs and taurocholate) directly in vitro, 25,26) suggesting that this drug can inhibit the processes of necrosis and apoptosis. In this study, we found that sucralfate inhibits gastric irritant-induced necrosis in vitro.…”
mentioning
confidence: 99%
“…In an ethanol-induced gastric injury model, the efficacy of SOS was reported to be weaker than that of sucralfate 26 . Additionally, an in vitro study showed that treatment with SOS alone cannot alleviate acid damaged-cultured cells 27 . However, several reports have indicated that SOS shows therapeutic effects in various oesophagitis models.…”
Section: Discussionmentioning
confidence: 99%